Media Pembelajaran Ilmu Fiqih Menggunakan Metode Contextual Teaching and Learning Untuk Meningkatkan Minat Belajar Santri - Umary, Siddiq (Jurnal Sistem Informasi dan Teknik Informatika (JAFOTIK), 2023)
Today's technology is developing very rapidly so that conventional learning methods can be hybrid with technology-based learning methods. The process of learning jurisprudence at the Jami'atul Qurro' Islamic Boarding School in Palembang still uses conventional methods, namely the teaching and learning process between Santri and Ustadz is only carried out through meetings in the classroom. Therefore, to be able to help teachers distribute their teaching materials to make them more interactive and informative, without having to be in class and to increase students' interest in learning, a Fiqh Science Learning Media Application based on the Contextual Teaching and Learning (CTL) Method is used. With this learning media, it is hoped that it will make it easier for students to repeat the material explained by Ustadz wherever and whenever so that it can increase students' interest in learning at the Jami'atul Qurro' Palembang Islamic Boarding School.